Virtual Prototype of Innovative Ka-Band Power Amplifier Based on Waveguide Polarizer - Fantauzzi, S.; Valletti, L.; Di Paolo, F. (Advanced Electromagnetics, 2020)
This paper outlines an innovative approach to design a spatial power-combining structure based on waveguide polarizers. It presents the 3D CAD model of the new structure with the transversal probes and considerations in positioning and optimization of them. Exploiting the transformation of the dominant input mode TE10 into an elliptically polarized wave, provided by the polarizer, it has been possible to achieve a division of power by eight, completely carried out in space. With the insertion of the transversal probes made by microstrips, the RF signal can be sent to the MMIC solid state power amplifiers, and then recombined in the output section. Thanks to the large number of power divisions made in the waveguide section, the insertion loss of the power divider/combiner is less than 0.5 dB across the 32-34 GHz band, achieving a great power density as well. At the Author’s best knowledge, this is the first work where a waveguide polarizer is used in Spatial Power Combining technology.